Analysis of oral dietary supplement use in rural older adults. Issue 9 (17th January 2019) - Shade, Marcia Y.; Witry, Matthew; Robinson, Katie; Kupzyk, Kevin
Abstract: Aims and objectives: To describe and explore characteristics associated with oral dietary supplement use and identify potential interactions with prescription medications in a sample of rural community‐dwelling older adults. Background: Older adults use polypharmacy to help manage chronic diseases. Due to healthcare access disparities, rural older adults may consider dietary supplement use as an alternative approach to maintain health and manage disease. Oral dietary supplement use is expected to increase among ageing adults; placing them at risk for potential interactions and adverse events. Design: A secondary analysis was conducted on oral dietary supplement, medication and health characteristic data collected on N = 138 participants. The original study was adherent to STROBE guidelines. Results: Researchers found that 83% of the rural older adults used oral dietary supplements in addition to their prescribed medications. Participants took additional single‐dose vitamins along with their multivitamin; 57% took vitamin D, 52% took calcium, 15% took vitamin C and 13% took additional potassium and vitamin E. Participants also used oral dietary supplements with medications that had a potential for interaction. Conclusions: Compared with national samples of older adults, a high percentage of rural older adults used oral dietary supplements in addition to their prescribed medications. In the rural setting, older adults are at risk for potential drug–oral dietary supplement interactions. Relevance to clinical practice: Nurses can conduct vigilant medication reconciliation that includes documenting characteristics of oral dietary supplement use. Nurses can assist with providing appropriate dietary supplements education that promotes patient knowledge and prevent inappropriate use; particularly when caring for older adults from rural settings.